The influence of magnetic order on the magnetoresistance anisotropy of Fe1 + δ–x CuxTe. (9th June 2017) - Helm, T; Valdivia, P N; Bourret-Courchesne, E; Analytis, J G; Birgeneau, R J
Abstract: We performed resistance measurements on F e 1 + δ − x Cu x Te with x E D X ⩽ 0.06 in the presence of in-plane applied magnetic fields, revealing a resistance anisotropy that can be induced at a temperature far below the structural and magnetic zero-field transition temperatures. The observed resistance anisotropy strongly depends on the field orientation with respect to the crystallographic axes, as well as on the field-cooling history. Our results imply a correlation between the observed features and the low-temperature magnetic order. Hysteresis in the angle-dependence indicates a strong pinning of the magnetic order within a temperature range that varies with the Cu content. The resistance anisotropy vanishes at different temperatures depending on whether an external magnetic field or a remnant field is present: the closing temperature is higher in the presence of an external field. For x E D X = 0.06 the resistance anisotropy closes above the structural transition, at the same temperature at which the zero-field short-range magnetic order disappears and the sample becomes paramagnetic. Thus we suggest that under an external magnetic field the resistance anisotropy mirrors the magnetic order parameter. We discuss similarities to nematic order observed in other iron pnictide materials.